AI-aided IoT technologies and applications for smart business and production - Khang, Alex; Misra, Anuradha; Gupta, Shashi Kant; Shah, Vrushank (CRC Press, 2024)
"This book covers the need for IoT technologies and AI-aided IoT solutions for business and production. It shows how IoT-based technology uses algorithms and AI models to bring out the desired results. AI-Aided IoT Technologies and Applications for Smart Business and Production, shows how a variety of IoT technologies can be used towards integrating data fabric solutions, and how intelligent applications can be used to greater effect business and production operations. The book also covers the integration of IoT data-driven Fintech applications to fulfil the goals of trusted AI-aided IoT solutions. Next, the authors show how IoT-based technology use algorithms and AI models to bring out the desired results across various industries including smart cities, buildings, hospitals, hotels, homes, factories, agriculture, transportation, etc. The last part focuses on AI-aided IoT techniques, Data analytics and visualization tools. This book targets a mixed audience of specialists, analysts, engineers, scholars, researchers, academics, professionals. It will be useful to Engineering officers, IoT and AI engineers, Engineering and Industrial Management students and Research scholars looking for new ideas, methodologies, technologies, models, frameworks, theories and practices to resolve the challenging issues associated with the leveraging IoT Technologies, Data-driven Analytics, AI-aided Models, IoT Cybersecurity, 5G and Sensors, and AR/VR Techniques for developing smart systems in the era of Industrial Revolution 4.0"--